How to interpret statistical analysis results implicated in health causality studies? - Nelsa María Sagaró del Campo; Larisa Zamora Matamoros (Medisur, 2020)
The improvement of statistical techniques is a research problem which does not lose its validity. Once it was identified and founded the use of the statistical analysis involved in the search for possible causal factors in health, it was necessary to design a methodology for its optimal application, in which the most complex stage turned was result interpretation. Therefore, this work aims at describing how to perform this interpretation, whose base is founded on literature theoretical references, and the practical ones, based on the experiences acquired from the various case studies and controls with the application of the technique. Indices, tables and graphs of the type are presented in the interpretation, similarity and cohesive trees, and implicative graph, from which the possible causal factors, confusing variables, effect modifiers and others that are identified and others which could be involved.